1975
DOI: 10.1055/s-0028-1106278
|View full text |Cite
|
Sign up to set email alerts
|

Der optimale Zeitpunkt der Behandlung des Kryptorchismus

Abstract: In a ten-year span (1950-1960) a total of 133 patients were operated upon for maldescent of testes. A follow-up enquiry traced 102, of whom 79 were re-examined. Maldescent had been unilateral in 71, bilateral in eight. All of the latter were infertile. In the others the fertility rate was the greater the younger the patient at the time of operation, best results being noted in those operated upon during the first or second year of life. Acquired testicular disorders seemed to play a minor role, while the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
4

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 0 publications
2
20
1
4
Order By: Relevance
“…hCG is known to induce Leydig cell differentiation and stimulate the production of testosterone [2]. Lackgren and Ploen did not find any morphological signs of maturation in the germ cells or Sertoli cells after five weeks of hCG-treatment [22]. This is in contrast to reports of the differentiation of Sertoli cells and the transformation of germ cells to primary spermatocytes after long term (3-6 months) hCG-treatment [2, 261.…”
Section: Germ Cell Adenylyl Cyclasecontrasting
confidence: 54%
“…hCG is known to induce Leydig cell differentiation and stimulate the production of testosterone [2]. Lackgren and Ploen did not find any morphological signs of maturation in the germ cells or Sertoli cells after five weeks of hCG-treatment [22]. This is in contrast to reports of the differentiation of Sertoli cells and the transformation of germ cells to primary spermatocytes after long term (3-6 months) hCG-treatment [2, 261.…”
Section: Germ Cell Adenylyl Cyclasecontrasting
confidence: 54%
“…Ludwig and Potempa [8] found that the fertility rate is inversely proportional to the age of the patient at the time of operation with best results being noted in those unilateral cryptorchid men operated upon during the first or second year of life. This 1975 study led to the conclusion that the optimal time for operating on testicular maldescent is (at the latest) the end of the second year of life.…”
Section: Discussionmentioning
confidence: 99%
“…These studies originated from the time when treatment was given relatively late, which may be the reason why semen quality was so poor and why treatment had a positive influence in only 25% of bilateral cases and showed no effect in those who had a unilateral undescent. In studies involving children operated on before the age of 3 or 6 years, orchidopexy has been associated with positive effect on semen quality [42, 44, 45]. Treatment of a unilateral undescended testis at the postpubertal age is associated with azoospermia or oligozoospermia in 85% of cases [46].…”
Section: Pathology In Maldescended Testesmentioning
confidence: 99%